THE WORK” HISTORY OF ANBIO AND HUKAMO": DIFFERENCES BETWEEN PUBLICATIONS (American Journal of Pedagogical and Educational Research, 2024)
The article describs the opinion about differentions on the publications of Alisher Navoi’s historical writing called “Tarihi anbiyo va hukamo”.